Isolated Persistent Left Superior Vena Cava, Sick Sinus Syndrome, and Challenging Pacemaker Implantation - Hatice S. Kemal; Aziz Gunsel; Levent Cerit; Murat Kocaoglu; Hamza Duygu (Case Reports in Cardiology)
Persistent left superior vena cava with absent right superior vena cava is a very rare venous anomaly and is known as isolated PLSVC. It is usually an asymptomatic anomaly and is mostly detected during difficult central venous access or pacemaker implantation, though it could also be associated with an increased incidence of congenital heart disease, arrhythmias, and conduction disturbances. Herein, we describe a dual-chamber pacemaker implantation in a patient with isolated PLSVC and sick sinus syndrome.